2019
DOI: 10.1002/smll.201903363
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuity‐Enhanced Thin Film Electrocatalytic Oxygen Evolution

Abstract: splitting, low-cost and facile fabrication of electrocatalysts, active for oxygen evolution reaction (OER) without involving precious metals (e.g., Ru and Ir), is therefore the central interests. [8,9] General approaches and knowledge capable of enhancing atom-efficiency in OER are also essential to conserve all the elements used in electrocatalysts regardless the individual nature abundance.As compared to colloidal electrocatalysts, scalable thin film electrocatalysts have been recognized by rapid mass transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 49 publications
(65 reference statements)
2
20
0
Order By: Relevance
“…In the corresponding LSV curve, the second oxidation peak (E pa2 ) appeared in the potential window of 0.30-0.50 V for the oxidation of Co(III) to Co(IV). It was reported that one of the peaks of CoO 2 species appears approximately at 570-585 cm À1 , [47][48][49] and the broad peak characteristic at high potentials (>0.30 V) in this work is consistent with the results in literature, indicating that CoO 2 phase appears. Furthermore, a small peak appearing at 476 cm À1 at 0.30 V and above more clearly indicates the generation of CoO 2 .…”
Section: In Situ Raman Spectroscopy Of Nico Dhs Catalystssupporting
confidence: 92%
“…In the corresponding LSV curve, the second oxidation peak (E pa2 ) appeared in the potential window of 0.30-0.50 V for the oxidation of Co(III) to Co(IV). It was reported that one of the peaks of CoO 2 species appears approximately at 570-585 cm À1 , [47][48][49] and the broad peak characteristic at high potentials (>0.30 V) in this work is consistent with the results in literature, indicating that CoO 2 phase appears. Furthermore, a small peak appearing at 476 cm À1 at 0.30 V and above more clearly indicates the generation of CoO 2 .…”
Section: In Situ Raman Spectroscopy Of Nico Dhs Catalystssupporting
confidence: 92%
“…It is most likely an amorphous oxyhydroxide layer, similar to those formed on different metals. [34][35][36][37] This gradient distribution of elements across the thickness of the film avoids the formation of a sharp interface between Zn and the surface passivation layer, thus ensuring good adhesion as it minimizes residual stress, which is beneficial for the stability of the layer during electrochemical operations.…”
Section: Resultsmentioning
confidence: 99%
“…2,11 To recognize the occurrence of potential-dependent reconstruction, operando characterization techniques (such as X-ray, Raman, FTIR, etc.) 10,12,13 are needed, but they are not easy to accomplish since skillful operation and expensive instruments are required. The most common index of OER activity in the literature is probably the overpotential, which is a potential gap on top of the thermodynamic minimum of 1.23 V to drive the OER at a certain current density (usually 10 mA cm −2 ).…”
mentioning
confidence: 99%